People's Republic of China-Hong Kong Special Administrative Region1 : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper analyzes the long-term fiscal policy in Hong Kong Special Administrative Region (SAR) and the anticipated structural changes in the economy. The paper examines the factors that contributed to the stability of the banking system in Hong Kong SAR by assessing the roles played by banks, equity markets, and debt markets. The study describes a procedure to extract the probability distribution of future exchange rate movements based on currency option data. The paper also provides a statistical appendix report of the country.